1985
DOI: 10.1063/1.448387
|View full text |Cite
|
Sign up to set email alerts
|

A Raman scattering study of the pressure induced phase transition in s-triazine

Abstract: The pressure induced phase transition in s-triazine has been studied using Raman scattering. Some of the features observed in a previous Raman scattering study of the phase transition at atmospheric pressure have also been observed in the present case, and a preliminary analysis based on an estimated form of the pressure dependence of the order parameter is reported. However, the data presented in the present study can not yet be fully reconciled with the corresponding results at atmospheric pressure. It is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In this study, we first analyzed the observed Raman frequencies of mode II [10] by using a polynomial a a P a P 2…”
Section: Calculations and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we first analyzed the observed Raman frequencies of mode II [10] by using a polynomial a a P a P 2…”
Section: Calculations and Resultsmentioning
confidence: 99%
“…As pointed out previously [10], the low-frequency E g mode in phase I (T<T c ) splits into the Raman bands I and II in phase II (T<T c ). The Raman band III is due to the molecular motions, which is observable in phase II (T<T c ) only [17].…”
Section: *Corresponding Authormentioning
confidence: 86%
See 3 more Smart Citations